Efficacy of Fiscal and Monetary Policy in Sierra Leone: An ARDL Bound Testing Approach - Tarawalie, Abu Bakarr; Kargbo, Noah (International Journal of Economics and Financial Issues, 2020)
This paper empirically examines the relative effectiveness of fiscal and monetary policies on economic growth in Sierra Leone. The study utilizes annual time series data, spanning from 1980 to 2017, within an Autoregressive distributed Lag (ARDL) Bound Testing estimation framework popularized by Pesaran and Shin (1998). The unit root test results show that all the variables are integrated of order one, i.e. I(1), and the cointegration bound testing results confirm the existence of cointegration amongst the variables. The study reveals that monetary policy is more effective than fiscal policy in promoting economic growth in Sierra Leone. Specifically, the findings show that money supply, real exchange rate and inflation are the significant variables that influence economic growth in the long run. Whilst the finding shows a positive relationship between money supply and economic growth, it however reveals a negative relationship for both real exchange rate and inflation on growth during the study period. The short run dynamics also reveals that money supply, government revenue, government expenditure and war dummy are the main variables influencing real GDP growth in Sierra Leone. Furthermore, the result shows that 24% of the disequilibrium in real GDP is corrected within a year. The study recommends that monetary and fiscal policies should be well coordinated and government should implement a balanced budget in order to overcome the issue of fiscal dominance in the Sierra Leone economy. Keywords: Economic growth, fiscal policy, monetary policy, Autoregressive distributed lag, Sierra Leone JEL Classifications: E52, E62, E63, C50, P24 DOI: https://doi.org/10.32479/ijefi.9407